The complex age of orthogneiss protoliths exemplified by the Eoarchaean Itsaq Gneiss Complex (Greenland): SHRIMP and old rocks - Horie, Kenji; Nutman, Allen; Friend, Clark; Hidaka, H (Precambrian Research)
Field studies integrated with cathodoluminescence petrography and SHRIMP U-Pb dating of zircons from >150 orthogneisses and metatonalites from the Eoarchaean Itsaq Gneiss Complex (southern West Greenland) shows that only a minority contain ≥3840. Ma zir